Nesting behavior of Bornean immature Orangutan (Pongo pygmaeus wurmbii) in Nyaru Menteng Arboretum School, Palangka Raya, Central Kalimantan, Indonesia - Fouad Fauzi; Soemarno Soemarno; Aminudin Afandhi; Amin Setyo Leksono (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fauzi F, Suemarno, Afandhi A, Leksono AS. 2020. Nesting behavior of Bornean immature Orangutan (Pongo pygmaeus wurmbii) in Nyaru Menteng Arboretum School, Palangka Raya, Central Kalimantan, Indonesia. Biodiversitas 21: 2172-2179. This research aimed at analyzing the nesting behavior of Bornean Orangutan (Pongo pygmaeus wurmbii) in Nyaru Menteng Arboretum, Palangka Raya, Central Kalimantan, Indonesia. The objects of observation were the immature orangutan nest, and the type of nest tree. The purposive sampling technique was used because not all immature Orangutan could make a nest. The Focal animal sampling method was used to determine the daily behavior and nets building activity. It involved observing and recording the behavior of five young Orangutans over a certain period of time and analyzing the nest made. The results of the study established that the daily activity of immature Orangutan on an average sequentially ranges from feeding 17.18%, moving 23.92%, resting 26.34%, and social behavior 32.57%. The process of making a nest begins with finding a suitable branch, bending and breaking twigs, and then arranging the twigs and leaves as a mattress. The duration of building a nest was 5.00 to 6.44 minutes, the preferred nest tree was Palaquium xanthochymum and Shorea spp., and the direction of the nest more facing west.